Aboveground biomass estimation in tropical rain forest based on terrestrial laser scanning - Rasib, Abd. Wahid (2018)
Estimation of forest biomass is significant for measuring the roles of forests as carbon sources and for supporting sustainable forest management. However, tree biomass is difficult to measure directly over large area. Hence, this study presents an advanced technology non-destructive approach to produce biomass estimation at plot scale using terrestrial laser scanning data in tropical rainforest. This study was carried out in the forest campus of Forest Research Institute Malaysia (FRIM), Kepong, Selangor. Three plots were established with a circular shape of 25 meters radius for each plot and 360ºscanned by terrestrial laser scanner. The main tree attributes that will be measured is diameter at breast height that extracted by using terrestrial laser scanning and ground measurement of diameter at breast height at these three plot. As the results, the overall total of aboveground biomass using terrestrial laser scanning data is 38.68 ton per hectare while for overall total aboveground biomass of census data is 38.09 ton per hectare. Comparison analyses between biomass terrestrial laser scanning and biomass census indeed root mean square at 0.37 for three plots a t-test -1.206 (p = 0.233). As conclusions, terrestrial laser scanner techniques is potential to be used as a tool for plot scale aboveground biomass estimation in high density tropical rain forest.